Optical Model of Medium for the Numerical Imitation of Wave Surface Forming High-Intensity Reflected Radiant Energy; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Shefer O. V. Olga Vladimirovna (Optical Technology, 2016)
Title screen